Dynamics in a Nonautonomous Nicholson-Type Delay System. (11th May 2021) - Muhammadhaji, Ahmadjan; Halik, Azhar
Abstract : A kind of Nicholson-type delay system is considered. Several conditions on the ultimate boundedness, extinction, permanence, periodic solution, and global attractivity of the system are established by employing the inequality techniques and comparison method and constructing suitable Lyapunov functional.